2006
DOI: 10.1074/jbc.m604114200
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Intestinal Peptide and PACAP38 Control N-Methyl-D-aspartic Acid-induced Dendrite Motility by Modifying the Activities of Rho GTPases and Phosphatidylinositol 3-Kinases

Abstract: Dendrite morphogenesis is highly dynamic and characterized by the addition and elongation of processes and also by their selective maintenance, retraction, and elimination. Glutamate can influence these events via N-methyl-D-aspartic acid (NMDA) receptors. The neuropeptides vasoactive intestinal peptide and pituitary adenylyl cyclase-activating polypeptide-38 (PACAP38) affect neurogenesis and differentiation in the developing nervous system. We report here that the peptides and NMDA acted synergistically on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 61 publications
2
24
0
Order By: Relevance
“…Consistent with this finding, PACAP and PAC1-R mRNA expressions are transiently increased in the cortex and the hippocampus after traumatic brain injury (Skoglösa et al, 1999a;Stumm et al, 2007). Besides its neuroprotective activity, PACAP reduces the number of damaged axons after traumatic injury (Farkas et al, 2004;Tamá s et al, 2006), favors dendrite outgrowth through the Rho PITUITARY ADENYLATE CYCLASE-ACTIVATING POLYPEPTIDE GTPase and PI3-K pathways in response to neuronal activity (Henle et al, 2006) and enhances NMDA receptor activity (Macdonald et al, 2005), which probably contribute to functional recovery. PACAP also exerts a neuroprotective effect against retinal degeneration induced by carotid occlusion, kainic acid, and monosodium glutamate (Babai et al, 2005(Babai et al, , 2006Seki et al, 2006b;Atlasz et al, 2007Atlasz et al, , 2008.…”
Section: Kip2supporting
confidence: 66%
“…Consistent with this finding, PACAP and PAC1-R mRNA expressions are transiently increased in the cortex and the hippocampus after traumatic brain injury (Skoglösa et al, 1999a;Stumm et al, 2007). Besides its neuroprotective activity, PACAP reduces the number of damaged axons after traumatic injury (Farkas et al, 2004;Tamá s et al, 2006), favors dendrite outgrowth through the Rho PITUITARY ADENYLATE CYCLASE-ACTIVATING POLYPEPTIDE GTPase and PI3-K pathways in response to neuronal activity (Henle et al, 2006) and enhances NMDA receptor activity (Macdonald et al, 2005), which probably contribute to functional recovery. PACAP also exerts a neuroprotective effect against retinal degeneration induced by carotid occlusion, kainic acid, and monosodium glutamate (Babai et al, 2005(Babai et al, , 2006Seki et al, 2006b;Atlasz et al, 2007Atlasz et al, , 2008.…”
Section: Kip2supporting
confidence: 66%
“…53 (12) showed that a deletion of 99 amino acid (aa) residues from the ␦-catenin COOH-terminal (⌬C99), but not a deletion of 205 aa (⌬C205), retains its ability to interact with Cortactin. As RhoA combines with the glutamate receptors at the spine plasma membrane and NMDA receptor activation decreases the RhoA activity (55,56), the C terminus of ␦-catenin may affect the Rho activity by interacting with one or more of these newly identified proteins. It also would be interesting to examine whether Cortactin or 14-3-3 mediates ␦-catenin-dependent RhoA inactivation and dendritic spine morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The morphogenesis of dendrites is highly dynamic, and characterized by addition, elongation, but also maintenance and retraction of dendritic processes. In hippocampal neurons, a model system to study the establishment of neuronal polarity in vitro [Craig and Banker, 1994], NMDA-induced increased dynamics of dendrites and dendritic branches is accompanied by endogenous Rac activation and prevented by expression of N17Rac1 [Henle et al, 2006]. Rac1 has also been implicated in the regulation of growth cone collapse or expansion induced by different extracellular ligands [Jin and Strittmatter, 1997;Kuhn et al, 1999;Vastrik et al, 1999;Shekarabi et al, 2005].…”
Section: Rac Gtpases In Vertebrate Neuronal Developmentmentioning
confidence: 99%